Alih Kode dan Campur Kode dalam Novel Glen Anggara Karya Luluk HF - Lintang Bintari; Ita Kurnia; Lutfiatul Aminin (Institut Nalanda, 2023)
Language is a means of communication that is used by each individual. Language is something that is needed and has a very important role as an expression of the existing soul. This study aims to analyze code-switching and code-mixing in the Glen Anggara story novel by Luluk HF. The method in this research is descriptive qualitative which is carried out using document studies. The type of this research is in the form of fragments or quotations in the novel. The technique used in this research is the reading then note technique which is related to code switching and code mixing in the novel Glen Anggara Story by Luluk HF. The results of this study indicate that the Glen Anggara story has 54 quotes about code-switching and 16 quotes about code-mixing. But what is most dominant is the code switching in Glen Anggara's novel by Luluk HF which mixes Indonesian with English, Javanese, Korean and Arabic. However, the most dominant among the languages used for code switching in the novel is a mixture of Indonesian and English.